A self-sustaining approach to backup power systems for reliable electrical supply - Ismail, Mohd Muzafar; Ya’akop, Aiman Saufi; Ali, Adlan; Ramli, Mimi Faisyalini; Che Wan Mohd Zalani, Che Wan Mohd Faizal; Abdullah, Fauziah (Scientific Research Publishing, 2025)
This paper presents the design, simulation, and experimental validation of self-sustaining approach of an AC-DC-AC battery-supported backup power supply intended to provide uninterrupted power to low and medium-power critical loads during utility outages. The proposed system employs a conventional rectifier-battery-inverter topology with an enhanced control strategy that enables seamless transition between grid-connected and battery-supported operation while maintaining stable output voltage regulation. Circuit level simulations were carried out using Multisim and Proteus, followed by laboratory prototype testing to validate system behavior under normal operation and outage conditions. Simulation and experimental results demonstrate output voltage regulation within ±5% of the nominal value, reliable inverter operation during grid loss, and controlled battery discharge consistent with rated load conditions. The measured inverter efficiency reached approximately 85% - 88%, with close agreement between simulated and experimental waveforms. The results confirm that the proposed system operates in accordance with fundamental energy conservation principles, functioning as a grid charged battery inverter rather than an energy-generating system. Compared with conventional backup power supplies, the proposed design emphasizes improved operational continuity, modular implementation, and clear control logic, providing a practical and extensible platform for future integration of renewable energy sources or intelligent load management strategies.